2005
DOI: 10.1063/1.1863447
|View full text |Cite
|
Sign up to set email alerts
|

Displacement current detection of photoconduction in carbon nanotubes

Abstract: Using a capacitive photocurrent measurement technique, we demonstrate the ability of both semiconducting and metallic single wall nanotubes to function as photodetectors over a wide spectral range. We observe clear peaks in the photo induced displacement current of a nanotube-plated capacitor that correspond directly to the semiconducting and metallic transitions in the nanotube absorbance spectrum. The signal increases substantially as the carrier drift velocity is raised with applied bias. A large increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 16 publications
2
47
0
Order By: Relevance
“…Later, numerous studies put attention on the spatially-and spectrally-resolved photocurrent of individual CNT devices to explore the electron-hole pair generation and separation in semiconducting SWCNTs [46,47,48,49] and the nanophysics of individual CNT devices such as the formation of Shottky barriers at the CNT-metal electrode interfaces. [50,51,52] Although photoconductors based on individual CNTs are a useful platform to investigate the photophysics of nanodevices, the signal is too weak for practical photodetection due to the small absorption cross section.…”
Section: Cnt Photoconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, numerous studies put attention on the spatially-and spectrally-resolved photocurrent of individual CNT devices to explore the electron-hole pair generation and separation in semiconducting SWCNTs [46,47,48,49] and the nanophysics of individual CNT devices such as the formation of Shottky barriers at the CNT-metal electrode interfaces. [50,51,52] Although photoconductors based on individual CNTs are a useful platform to investigate the photophysics of nanodevices, the signal is too weak for practical photodetection due to the small absorption cross section.…”
Section: Cnt Photoconductorsmentioning
confidence: 99%
“…The photoresponse mechanism of these detectors was predominantly thermal effects, such as the bolometric effect [54] and the photothermolelectric effect, [55] as we will discuss in later sections. However, a technique known as capacitive photocurrent spectroscopy was adopted to study the photocurrent spectrum in individual CNTs [48] and in pure CNT films, [47] which can distinguish the photoconductive effect from the thermal effect. Results showed that in CNT films electronhole pairs can be dissociated into free carriers under large external electrical fields.…”
Section: Cnt Photoconductorsmentioning
confidence: 99%
“…2 Photoconductive detection is apparently very weak, 3 but Itkis et al 4 have reported a sensitive bolometric Near Infrared detector based on a carbon nanotube ͑CNT͒ film. Microwave detection using SWCNTs has been extended to 110 GHz.…”
mentioning
confidence: 99%
“…Optical characterization is performed using a recently developed capacitive photocurrent technique [14][15][16][17][18] . The sample is fixed to a copper block within an optical flow cryostat which is placed between the poles of an electromagnet.…”
Section: Methodsmentioning
confidence: 99%